Noninvasive measurements of tissue perfusion in critical limb ischemia Nicht invasive Messungen der Gewebedurchblutung bei kritischer Extremitätenischämie - Rother, Ulrich; Lang, Werner (Gefässchirurgie, 2018)
Critical limb ischemia (CLI) remains a challenge for an interdisciplinary therapeutic team due to chronic nonhealing wounds. Against this background, there is a necessity of quality control after revascularization. Beside the isolated evaluation of the macrocirculation by Ankle-Brachial or Toe-Brachial Index measurements, the microcirculation as an additional important factor of wound healing often remains underestimated. The following article gives an overview about the current investigation methods for noninvasive perfusion control of the CLI patient. Therefore, transcutaneous oxygen pressure (tcpO2), the “oxygen-to-see” method which is a combination of white light tissue spectrometry and laser-Doppler flowmetry, fluorescence angiography with indocyanine green, and multispectral optoacoustic tomography will be described.
CRIS-Team Scopus Importer:2025-10-27
Keywords: Critical limb ischemia; Fluorescence angiography; MSOT; O2C; tcpO